KAJIAN SURAT TELEGRAM TENTANG PENGEMBALIAN DANA KORUPSI TERHADAP UNDANG UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Iman Munandar Batuara; Ardiansah; Aulia Vivi Yulianingrum Bagio Kadaryanto (Collegium Studiosum Journal, 2025)
Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia requires a concept of criminal offense settlement that waives the criminal process for the sake of public order and security (Harkamtibmas) and the public interest. This serves as the juridical basis for the issuance of the Criminal Investigation Agency Telegram Letter Number: ST/206/VIII/2016 dated August 24, 2016, concerning the Handling of Corruption Crimes in the Return of State Financial Losses. This telegram letter explains that the reason for terminating an investigation based on the Criminal Investigation Agency Telegram Letter Number: ST/206/VIII/2016 dated August 24, 2016, is that if there is a return of state financial losses to the state treasury during the investigation process, the investigation shall not be upgraded to the prosecution stage. Investigators complete the administration for the termination of the investigation by referring to the Circular Letter of the Chief of the Indonesian National Police Number: SE/7/VII/2018 dated July 27, 2018, concerning the Termination of Investigation, issuing a Progress Report on Investigation Results (SP2HP) to the reporter, and sending a formal letter to the Resort Police (Polres). The purpose of this research is to analyze the review of the Telegram Letter concerning the return of corruption funds against Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. It also aims to analyze the ideal review of the Telegram Letter concerning the return of corruption funds against Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. The method used is normative legal research. Based on the research results, it is known that the review of the Telegram Letter concerning the return of corruption funds against Law Number 31 of 1999 concerning the Eradication of Corruption Crimes shows that the Telegram Letter can override the Law; if state losses are returned, the criminal offense will be terminated at the investigation stage. The existence of this Telegram Letter allows the return of state losses to halt the investigation, which contradicts Article 4 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, which states that the return of state financial or economic losses does not abolish the criminal prosecution of the perpetrator as referred to in Article 2 and Article 3. Ideally, the review of the Telegram Letter concerning the return of corruption funds against Law Number 31 of 1999 concerning the Eradication of Corruption Crimes should emphasize the return of state losses without abolishing the corruption crime itself. As an extraordinary crime, corruption possesses a higher complexity compared to conventional crimes or even other special crimes. Particularly in the investigation stage of corruption crimes, there are several authorized investigative institutions empowered to handle the investigative process against perpetrators involved in these corruption offenses.